Tuning the gas separation performance of fluorinated and sulfonated PEEK membranes by incorporation of zeolite 4A - Tahir, Z. (John Wiley and Sons Inc., 2018)
Mixed matrix membranes (MMMs) containing fluorinated-sulfonated poly(ether ether ketone) (F-SPEEK) and zeolite 4A filler, were prepared by solution casting. F-SPEEK with a fixed degree of sulfonation (40) was used for membrane synthesis. The SEM pictures showed good interfacial adhesion between filler particles and polymer, which was also confirmed by the increase in glass transition temperature of MMMs with increase in filler particles. Pure and mixed gas permeation experiments were carried out to investigate the potential of this membrane material. The results revealed that addition of zeolite 4A fillers enhanced both permeability and selectivity owing to the intrinsic nature of polymer and modified membrane morphology due to filler. The highest permeability obtained for CO2 at 30 filler loading was 49.2 Barrer, while highest selectivities obtained for CO2/CH4 and CO2/N2 were 55 and 58 compared to 47 and 51 for the unfilled polymer, respectively. Intrinsic CO2 solubility of F-SPEEK was observed to be decreased from 10.7 to 1.9 (10â2) cm3 (STP)/cm3Â cmHg with the addition of Zeolite 4A. Â© 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 45952. Â© 2017 Wiley Periodicals, Inc.